2019
DOI: 10.1108/tr-02-2018-0018
|View full text |Cite
|
Sign up to set email alerts
|

Smart destinations and tech-savvy millennial tourists: hype versus reality

Abstract: Purpose This paper aims to contrast the expectations placed on the smart destination as a theoretical management approach with the reality of emergent tech-savvy tourism demand by examining the response of this segment to three critical dimensions of technology use in the context of smart destinations. Tech-savvy tourists are here represented by highly educated Spanish millennial tourists. Design/methodology/approach Data were obtained through an online survey and analysed through descriptive techniques and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
98
0
12

Year Published

2020
2020
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 134 publications
(111 citation statements)
references
References 50 publications
(130 reference statements)
1
98
0
12
Order By: Relevance
“…As our research revealed, tourists used information technologies during their journey to a large extent. However, based on the research of Femenia-Serra, Perles-Ribes, et al (2018), the interaction is still very limited. The problem can be partially solved by using volunteered geographical information (VGI), which is a reliable source of Big data (Baggio & Scaglione, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…As our research revealed, tourists used information technologies during their journey to a large extent. However, based on the research of Femenia-Serra, Perles-Ribes, et al (2018), the interaction is still very limited. The problem can be partially solved by using volunteered geographical information (VGI), which is a reliable source of Big data (Baggio & Scaglione, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…It is generally recognized that the tourists-a crucial element and key actors of the ST ecosystem-are rather neglected by academic research [13,16,17]. Our study constitutes a contribution to addressing this research gap.…”
Section: Introduction: Overtourism Tourists' Behavior and Smart Tourmentioning
confidence: 92%
“…Academic research has been interested in the environmentally responsible behavior of tourists [7,10], as well as in the uses of social media (SM) by tourists [18,19]. Lately, scholars have also been interested in the field ST management framework, and have explored the related dimensions, issues and aspects [13,16]. This section focuses on sustainable and responsible behavior by tourists, the concept of smart tourists and the influence of SM/SNSs on tourist consumer behavior.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Information and Communication Technologies (ICTs) have revolutionized the hospitality and tourism industries [26]. As a result of the use of ICT, tourists are increasingly aware of the characteristics of the tourism offering and seek greater customization [27][28][29][30] (in addition, they are acquiring greater power through the use of technologies to co-create value with other stakeholders of that destination [31]).…”
Section: Sustainable Smart Tourism Destinationsmentioning
confidence: 99%
“…Like other young people, they are very attached to new technologies [77][78][79], use their smartphones for multiple purposes and use them throughout the various stages of their trip [31,41,80,81]. They download apps, such as apps that provide prayer times, especially in non-Muslim countries where there are no muezzins making the call to prayer over loudspeakers on mosques; apps that indicate the direction of Mecca so that the traveler can pray facing the right direction [82] (Fakhruroji 2018); and apps that geo-locate restaurants and places of worship.…”
Section: Characteristics Of the Muslim Market Segmentmentioning
confidence: 99%